Morphology optimization of highly oriented carbon nanotubes for bioengineering applications - Yousefi, A.T.; Kadri, Nahrizul Adib (Springer Verlag (Germany), 2016)
The remarkable properties of high oriented vertically aligned carbon nanotubes make them attractive for bioengineering applications. In this paper, we describe a process of growing long oriented CNTs arrays to improve the electrical properties of subsequent devices based on CNTs. Chemical vapour deposition (CVD) was used to deposit highly oriented CNTs with camphor oil as its carbon source, and argon as its carrier gas to grow perpendicular CNTs on the surface of a silicon substrate in the presence of ferrocene as a metallic catalyst. Images taken by the field emission electron microscopy (FESEM) indicate that the formation mechanism of oriented CNTs, with high morphological purity of nanotubes, depends significantly on the deposition time and applied temperature to the furnaces. This method might be an effective method to produce highly oriented multiwall carbon nanotubes at different aspect ratios.